Non-industrial private forest landowners` choices of timber management strategies and potential allowable cut : case of Pohjois-Savo - Pesonen, Mauno (Acta forestalia Fennica, ISSN 0001-5636, 1995)
Summary.
Keywords: metsänomistajat